THE INFLUENCE OF MINIMUM COMPLETENESS CRITERIA OF LEARNING MOTIVATION OF STUDENTS IN THE SUBJECTS OF CIVIC EDUCATION IN GRADES X STATE SENIOR HIGH SCHOOL - evvi ari widyawati; Berchah Pitoewas; Hermi Yanzi (Jurnal Kultur Demokrasi, 2012)
The purpose of this research to explain how the influence of minimum completeness criteria of learning motivation of students in the subjects of civic education in grades x state senior high school 1 seputih banyak lampung tengah in academic year  2012/2013. a method of research used in this research is a method of descriptive quantitative. a sample in this research total 50 people. Analysis of data using chi quadrat. Basic technique using questionnaire collecting data. Research showed that: (1) the influence minimum completeness criteria against motivation learning learners (x) dominant in the prologue pretty good with the percentage 50%, (2) motivation learning learners on the subjects civic education (y) dominant in the prologue strong rate 36%, (3) there are relations a positive, significant, and categories of the clinging high between influence minimum completeness criteria against motivation learning learners on the subjects civic education, it means better knowledge of minimum completeness criteria possible further improve motivation learning learners on the subjects civic education and it will achieve a feat goodKeywords: Minimal completeness criteria, Motivation, Civic Education